التمكین كمحور للتنمیة البشریة لمواجهة التحدیات المعاصرة للشباب في المجتمعات العربیة - سید لطیف هدى (Finance and Business Economies Review, 2018)
Empowerment means giving people the powers and responsibilities, encouraging them to participate and taking the appropriate decisions and giving them the freedom and confidence to do their work without the direct intervention of the administration, so it is primarily concerned with documenting the relationship between the administration and the employees, and helping to motivate them and participate in decision-making and break the administrative and organizational stalemate. Which makes the interest in the principle of youth empowerment an essential element for the success of countries and organizations in facing contemporary challenges.